Antimicrobial efficacy testing of antibiotic-containing biodegradable nanopolymers against biofilm and planktonic cells. - Polimyr Caesar Dave Pelisco Dingal. (2009)
Cystic fibrosis and rampant urogenital infections, caused by increasingly resistant microbial biofilms, call for more creative anti-infective systems. This study investigated the in vitro efficacy of levofloxacin (LEV)–loaded poly(D,L-lactide-co-glycolide) (PLGA) and poly-ε-caprolactone (PCL) nanopolymers against optimally-grown biofilms of Escherichia coli K12 W3110 and Pseudomonas aeruginosa PA01. High-throughput biofilm production and antimicrobial susceptibility testing were conducted in the Calgary Biofilm Device (CBD). Rich Luria-Bertani medium provided maximal accumulation of biofilm biomass, with optimum times (24 and 48 h, respectively) and temperatures (30 C and 21 C, respectively) found under dynamic culture conditions. For both pathogens, minimum inhibitory concentrations (MIC) of 2.8 µg/mL and 16.5 µg/mL total LEV load were found for LEV-PLGA and LEV-PCL, respectively. Minimum biofilm eradication concentrations (MBECs) improved at least 2-fold with increase in exposure time (48 hours) achieving LEV-PLGA MBECs of 1.4 and 0.2 µg/mL and LEV-PCL MBECs of 16.5 and 8.2 µg/mL for E. coli and P. aeruginosa, respectively. With efficient use of drug-encapsulated nanopolymers, bactericidal dosages are sufficiently lowered and dosing intervals can be extended due to the sustained drug release feature afforded by these efficacious nanocarriers.